On the Practical Applicability of the Li Metal‐Based Thermal Evaporation Prelithiation Technique on Si Anodes for Lithium Ion Batteries (Adv. Energy Mater. 3/2023). Issue 3 (20th January 2023) - Adhitama, Egy; Bela, Marlena M.; Demelash, Feleke; Stan, Marian C.; Winter, Martin; Gomez‐Martin, Aurora; Placke, Tobias
Abstract : Li Thermal Evaporation In article number 2203256, Egy Adhitama, Aurora Gomez‐Martin, and co‐workers evaluate the practical applicability of Li thermal evaporation as a pre‐lithiation technique on powder‐based Si in both Li metal cells and a full‐cell setup with lithium nickel cobalt manganese oxide (LiNi0.8 Co0.1 Mn0.1 O2, NCM‐811). This study deeply discusses the significant consequences of electrode capacity balancing (N:P ratio) with regard to prelithiation. The trade‐off between cell lifetime and energy density is also highlighted.